Spectroscopic Properties and Biological Activity of Fluphenazine Conjugates with Gold Nanoparticles - Oliwia Kowalska; Natalia Piergies; Anna Barbasz; Piotr Niemiec; Patrycja Gnacek; Dorota Duraczyńska; Magdalena Oćwieja (Molecules)
Fluphenazine (FPZ) is a well-known neuroleptic that has attracted considerable scientific interest due to its biocidal, virucidal, and antitumor properties. Although methods for encapsulating and delivering FPZ to enhance its activity and reduce side effects have been developed, there is still limited knowledge about its conjugates with gold nanoparticles (AuNPs). Therefore, the aim of this research was to develop a preparation method for stable FPZ-AuNP conjugates and to investigate their physicochemical and biological properties. FPZ-AuNP conjugates were synthesized via a ligand exchange process on the surface of gold nanoparticles (AuNPs) with an average size of 17 ± 5 nm. Electrokinetic measurements revealed that the zeta potential of FPZ-AuNPs is affected by both their composition and pH. The FPZ-AuNPs exhibited an isoelectric point due to the acid–base properties of FPZ. Surface-enhanced Raman spectroscopy (SERS), combined with density functional theory (DFT), was used to determine the adsorption structure of FPZ after conjugation. Studies with human neuroblastoma cells (SH-SY5Y) revealed that FPZ-AuNP conjugates more effectively reduced cell viability compared to citrate-stabilized AuNPs alone or free FPZ molecules. The reduction in SH-SY5Y cell viability was found to be dependent on the FPZ-AuNP concentration.